TRANSMUTATIONS OF PLOT AND CHARACTERS: A COMPARATIVE ANALYSIS OF THE ANIMATED FILM THE LION KING (1994) AND THE LIVE-ACTION THE LION KING (2019) - Wanda Andres Saputra; Asmanadia Izzatul Karimah; Zaidi, Abdullah (CrossOver, 2023)
This study aims to reveal the existence of transmutations of the plot and characters in the film adaptation. This study uses theory (Stam, Robert 2000) to find transmutations of plot and characters and theory (Hutcheon, Linda 2012) for a comparative analysis of the film adaptation of the animated version of "The Lion King (1994)" and the live-action version of " The Lion King (2019). In this study, the researcher used a descriptive-qualitative research method, and data collection was carried out visually and textually in the film. Based on Spradley's theory and analysis, the researcher first found that the transmutations in the plot are in the film adaptation, especially regarding the removal and addition of scenes that were not there before. Second, transmutations of characters occur in several characters, such as Zazu, Rafiki, Timon, and Pumbaa. As such Zazu in the animation, it is purple, while in live-action it is black. Then there are changes in the narration of the characters. Thus, this research finds that there are changes or transmutations to the plot and the characters in the film.